Economic substantiation of parameters of the technical facilities of a military unit to ensure their efficient operation - Osipenko, S. М. (Honor and Law, 2019)
The article describes how to determine the parameters of complex technical means in terms of their effective use for the intended purpose in combat and daily activities of military units, taking into account economic factors.